Task-based language teaching and the use of computer technology with the internet in ESL/EFL classrooms: Teachers' Perceptions - Misrah Hamisah, Mohamed (2012)
Student-centered, hands-on, practical and flexible approaches have becoming fundamental aspects in language education field recently. These features are in line with what task based language teaching (TBLT) can offer learners in their language learning. However, with the advent of information and communication technology (ICT), learners are increasingly exposed to web-based learning environment. Therefore, it is seen as crucial to find out the potential of ICT, namely computer technology and the Internet in providing a technology-mediated contextual for TBLT in an English language classroom. This article discusses the term TBLT in an ESL/EFL classroom and the use of computer technology with its in-built companion, the Internet as language learning tools. Teachers’ perceptions are important to see their readiness to implement both terms that have been discussed in their teaching practice. Thus, this article also put forward teachers’ perceptions on TBLT and the use of computer technology with the Internet in an English language classroom. Finally, based on the study of teachers’ perceptions on both areas, this article ends in revealing the possibilities that teachers have in order to incorporate TBLT and the use of computer technology with the Internet in an ESL/EFL classroom.